As novas relações Estado-sociedade: o papel desempenhado pelos movimentos sociais no Brasil e na Argentina - Silva, Maria Erondina Silveira da (2007)
Through explanatory analysis, this dissertation works the aspects referring to the autonomy of the State-Nations and the functions played by the social contemporary movements especially in Brazil and Argentina and where up to a certain point these are instruments capable to propitiate citizenship and a participant democracy in addition having the capacity to insert socially some segments that find difficulties to participate in the productive process. For this reason, it is necessary to define social movement as an instrument capable of considering the different individual expectations for an entire group of the population, taking in consideration the differences in gender, age, income, culture and the access if the basic rights, along with others. From the participation of individuals, the advances begin to constitute conquests and no more concessions of the of the power holders. From this point, the relevance of the new social actions as instruments of construction of a experienced citizenship, for being seeds of the conquest and for having as a purpose the capacity of creating social standards that do not exclude individuals but that promote and respect the diversities. Since the latest actions of the State-Nations are in the definition of domestic politics increasingly articulated in a level of regional blocks, local alternatives can represent the creation of new spaces of politics and democratic construction. This way, the civil society can generate through social movements areas of negotiation in which the decisions are formed in favor of the social welfare. That is, not only relegating to the States the monopoly of the decisions.